2011
DOI: 10.1111/j.1365-2796.2011.02369.x
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 as a predictor of infarct transmurality and functional recovery in patients with myocardial infarction

Abstract: Abstract. Andrassy M, Volz HC, Riedle N, Gitsioudis G, Seidel C, Laohachewin D, Zankl AR, Kaya Z, Bierhaus A, Giannitsis E, Katus HA, Korosoglou G (University of Heidelberg, Heidelberg, Germany). HMGB1 as a predictor of infarct transmurality and functional recovery in patients with myocardial infarction. J Intern Med 2011; 270: 245-253.Objectives. High-mobility group box 1 (HMGB1) protein is an innate danger signal for the initiation of host defence and tissue repair. The aim of this study was to analyse serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 42 publications
1
45
0
4
Order By: Relevance
“…12,32) Previous studies have shown that HMGB1 functions as a pro-inflammatory cytokine in certain cardiovascular diseases, and it was related to the severity of coronary artery disease. 33,34) Yao, et al demonstrated that myocardial expression of HMGB1 significantly increased in rats with acute MI. 35) High serum levels of HMGB1 may cause cardiac inflammation and left ventricular dysfunction after MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,32) Previous studies have shown that HMGB1 functions as a pro-inflammatory cytokine in certain cardiovascular diseases, and it was related to the severity of coronary artery disease. 33,34) Yao, et al demonstrated that myocardial expression of HMGB1 significantly increased in rats with acute MI. 35) High serum levels of HMGB1 may cause cardiac inflammation and left ventricular dysfunction after MI.…”
Section: Discussionmentioning
confidence: 99%
“…This is because its active release by mononuclear cells and passive release from necrotic or damaged cells. 34) It has been reported that there are several patents proposed for controlling the production, secretion and neutralization of HMGB1 and consequently the inflammatory process. Among them, anti-HMGB1 antibodies and HMGB-A box as a competitive antagonist of HMGB1 are the most reliable methods to regulate HMGB1 directly.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has focused on the role of HMGB1 in various cardiac and metabolic stress models characterizing HMGB1 as an important initiator of inflammation and fibrosis (6,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 has been identified as a novel pro--inflammatory cytokine in several cardiovascular diseases [3][4][5][6]. Recently, HMGB1 has been found to function as an early pro-inflammatory mediator during myocardial ischemia and reperfusion (I/R), as well as some classical early pro-inflammatory Gangying Hu et al, Exendin-4 and HMGB1 cytokine such as tumor necrosis factor-a (TNF-a), interleukin-6 (IL-6) and could promote the release of TNF-a and IL-6, whereas HMGB1 A box peptide (a specific HMGB1 antagonist) could protect against myocardial I/R injury and inhibit the release of TNF-a and IL-6 [3], while inflammatory response is considered to be a critical factor of myocardial I/R injury [7,8].…”
Section: Introductionmentioning
confidence: 99%